Work Readiness of Program X Awardees: An Overview of Facing the Professional World - Pratama, Muhammad Yoga (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2024)
The unemployment rate among university graduates in Indonesia remains a serious issue that impacts economic and social stability. One of the main factors influencing this is the work readiness of graduates. This study aims to analyze the work readiness of awardees of Program X, a professional training program for second- and third-year university students in Indonesia. This study employs a descriptive quantitative approach with univariate analysis. Data were collected through a questionnaire based on a work readiness scale that includes four main aspects: personal characteristics, organizational acumen, work competence, and social intelligence. The findings indicate that most awardees have low work readiness, with significant differences between male and female participants, where males tend to be more prepared than females. These findings highlight the need for improvements in the training methods of Program X, particularly in terms of industry involvement and hands-on training. The implications of this study are expected to serve as a basis for the development of more effective education and job training policies and provide insights for further research on other factors affecting graduate work readiness.